1998
DOI: 10.3319/tao.1998.9.4.655(t)
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variation of Fractal Parameters and Its Geological Implications

Abstract: The spatial variation of the fractal dimension and its geologic implica tions are studied using an empirical approach. The fractal parameters, including the surface's fractal dimension, D .. the angular fractal dimensur[� sion, D , the gamma ( y) value and the break-distance (R), are derived by ang the variogram method. Synthetic surfaces are generated by the successive random addition (SRA) method by assigning different values to the Hurst exponent. Two test sites were selected to study the link between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…The accuracy of the digital elevation model could also be an influential factor in scale-dependent variation and directional bias of fractal dimension. Nevertheless, the angled variograms are picking up detail that is not visible in a contour plot and might extract the anisotropy of the terrain feature that reflects the regional structures of valleys and ridges (Klinkenberg and Goodchild, 1992;Sung et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The accuracy of the digital elevation model could also be an influential factor in scale-dependent variation and directional bias of fractal dimension. Nevertheless, the angled variograms are picking up detail that is not visible in a contour plot and might extract the anisotropy of the terrain feature that reflects the regional structures of valleys and ridges (Klinkenberg and Goodchild, 1992;Sung et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (1999a,b) divide the study area of the entire Taiwan Island into different sizes of units and find a good estimation of the fractal dimension with a unit size as small as 1280 Â 1280 m 2 (32 rows by 32 columns). In an empirical approach, Sung et al (1998) suggested 30 by 30 be the smallest data matrix from which one can obtain about 80% accuracy in estimating the surface fractal dimension. Referring to the conventional DEMs of Taiwan, the smallest spatial unit is therefore about 1.2 by 1.2 km for estimating the fractal parameters of the landscape surface.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations